New cave-dwelling pseudoscorpions of the genus Lagynochthonius (Pseudoscorpiones, Chthoniidae) from Guizhou in China - Hou, Yanmeng; Feng, Zegang; Zhang, Feng (Zootaxa, 2023)
Eleven new Lagynochthonius species from thirteen karst caves of Guizhou Province are described, including detailed diagnosis and illustrations: L. biyunensis sp. nov. from Biyun Cave (Panzhou City), L. guanniuensis sp. nov. from Guanniu Cave (Xifeng County), L. latipectus sp. nov. from Xianren Cave and Shenxian Cave (Jiangkou County), L. longedentatus sp. nov. from Hongbaituo Cave (Ceheng County), L. longyanensis sp. nov. from Longyan Cave (Bozhou District), L. maanensis sp. nov. from Pianxiao Cave (Zheng’an County), L. mawangensis sp. nov. from Mawang Cave (Wuchuan County), L. nigriculus sp. nov. from Yuqiyan Cave and unnamed cave (Weining County), L. tuoluoensis sp. nov. from Tuoluodadong Cave (Shuicheng District), L. xiaoensis sp. nov. from Xiao Cave (Suiyang County) and L. zhijinensis sp. nov. from Long Cave (Zhijin County). All species are endemic to Guizhou. An identification key to all known Lagynochthonius species from China is also provided.